Предмет: Алгебра,
автор: seitakov80
Упростите выражение:
Sin(П-2a) - Tg(П+a)=
Ответы
Автор ответа:
0
Упростите выражение:Sin(П-2a) - Tg(П+a)=
Sin(П-2a) - Tg(П+a)=Sin(2a) - Tg(a)= 2Sin(a)cos(a) -Sin(a)/cos(a)=
или можно так
[2Tg(a)]/(1+Tg²(a)) - Tg(a)= tg(a)[ (1-tg²(a))/(1+tg²(a))]
Sin(П-2a) - Tg(П+a)=Sin(2a) - Tg(a)= 2Sin(a)cos(a) -Sin(a)/cos(a)=
или можно так
[2Tg(a)]/(1+Tg²(a)) - Tg(a)= tg(a)[ (1-tg²(a))/(1+tg²(a))]
Автор ответа:
0
а после равно, как дальше?
Похожие вопросы
Предмет: Английский язык,
автор: KhoroshyiD
Предмет: Алгебра,
автор: anastasya160906
Предмет: Математика,
автор: kundyzajzubatkan
Предмет: География,
автор: tarasyan999
Предмет: Информатика,
автор: sergantrus98